The Interpretation Mechanism of Meaning Creation Ways in German Literary Discourse - Balabaeva, Yuliya; Skokova, Tatiana; Voronina, Larisa; Melnikova , Yuliya; Yarygina , Olga (Jordan Journal of Modern Languages & Literatures, 2023)
This research studies the meaning interpretation mechanism used by the reader of a literary text. The work was carried out in the framework of the cognitive scientific approach, known in the science as Discourse Processing. The article is focused on the process of both understanding the depicted model of the situation, as well as the process of extracting the actual emotional and evaluative shades of meaning. It emphasises the way the meaning creation process is fulfilled in German literary discourse. Every moment of a reader’s perceiving information is coupled with a certain stage of understanding the text: a word – separate syntagmatic constructions, sentences and their progression – a systemic concept/ image of the situation model presented in the text. At every stage of the processing, text information collaborates with the recipient’s knowledge asset. On the one hand, new information is accumulated with this interaction and steadily gets connected to the existing knowledge. At the same time, the activated pre-knowledge structures coordinate the way of perceiving the incoming information enabling the extension of the limited abilities of working memory. This makes cognition of the organizing inception of transmitting of common meaning as well as its differential features possible. In other words, the stages letting interpretation of the meaning of verbal text information are comprised of the following phases: 1) interpretation of the neutral meaning; 2) analysis of expressing the attitude to reality from the standpoint of its cognitive content, i.e. its moduses (“understanding”, “imagination”, “reminiscence/ recollection”, “volition”) – the most significant brain and thinking activities explicated during speech-thinking process and mainly conditioned by linguistic peculiarities of languages of different type specification; 3) specification which is based on the phenomenon of polymodality and accompanied by transitions of semantic components of the image; 4) generation of a categorical and conceptual level of concepts. With the help of the examples taken from the author’s German literary discourse, the research paper illustrates such a model of meaning structuring. Namely, it shows the way the correlation between the levels of concept, the verbalisation of which is done by a system of expression means of evidentiality as the means of conceptualisation and categorization of the world in the language, and the modus categories not possessing their information about the world becomes the base of extracting the implied meanings.